How life history affects threat status: Requirements of two Onobrychis-feeding lycaenid butterflies, Polyommatus damon and Polyommatus thersites, in the Czech Republic - Šlancarová, Jana (Jihočeská univerzita, 2015)
The study compares ecological requirements of two related (congeneric) butterflies, Polyommatus damon and P. thersites, both of them reaching their northern distribution margins in Central Europe, where they co-occur on xeric grasslands, utilising identical larval host plants. Despite these similarities, one of them is substantially more endangered than the other. We describe their egg-laying behaviour and egg placement patterns, and analyse their distribution in a model landscape, showing that minute life history details affect differing species' fates in human-dominated landscapes.
How life history affects threat status: Requirements of two Onobrychis-feeding lycaenid butterflies, Polyommatus damon and Polyommatus thersites, in the Czech Republic
Keywords: buttery conservation; farmland landscape; grazing; habitat management insect life history; Lepidoptera; metapopulation; xeric grassland; buttery conservation; farmland landscape; grazing; habitat management insect life history; Lepidoptera; metapopulation; xeric grassland